Dynamic contrast-enhanced magnetic resonance imaging of masticatory muscles in patients with idiopathic condylar resorption - Yu-Chen Wang; Hsiao-Chiao Yeh; Yunn-Jy Chen; Tiffany Ting-Fang Shih (Journal of Dental Sciences, 2025)
Background/purpose: Idiopathic condylar resorption (ICR), a subset of temporomandibular disorders (TMDs), presents an unclear relationship between structural changes in the mandibular condyle and alterations in masticatory muscle perfusion. This study aimed to investigate the correlation between mandibular condyle structural changes and masticatory muscle perfusion in patients with ICR using dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI). Materials and methods: From July 2018 to August 2022, patients with ICR from hospital-based TMD clinics underwent conventional and DCE MRI examinations. The patients were categorized on the basis of the degree of temporomandibular joint (TMJ) condylar resorption into grade 0 (normal), grade 1 (mild to moderate), and grade 2 (severe). DCE MRI parameters of masticatory muscles responsible for mouth closing (masseter [MA] and medial pterygoid [MP]) and opening (lateral pterygoid [LP]) were examined. Results: Among 79 patients (158 TMJs), 41 % were assigned to the grade 0 group, 29 % were assigned to the grade 1 group, and 30 % were assigned to the grade 2 group. No significant differences in demographic or physical parameters were observed between the groups. In cases of severe condylar resorption (grade 2), the LP muscle exhibited a marked increase in plasma volume; none of the other muscles exhibited significant variations in plasma volume. Conclusion: Increased plasma volume perfusion of the LP muscle is correlated with the severity of TMJ condylar resorption, indicating a specific correlation between muscle function and ICR severity. DCE MRI is useful for exploring muscular adaptation in patients with ICR and TMDs.